Increased Production of 11β-hydroxysteroid Dehydrogenase Type 2 in the Kidney Microsomes of Squirrel Monkeys (Saimiri spp.) - Sadosky, Patti W (American Association for Laboratory Animal Science, 2008)
In squirrel monkeys (Saimiri spp.), cortisol circulates at levels much higher than those seen in man and other Old World primates, but squirrel monkeys exhibit no physiologic signs of the mineralocorticoid effects of cortisol. These observations suggest that squirrel monkeys have mechanisms for protection of the mineralocorticoid receptor (MR) from these high levels of cortisol. We previously showed that the serum cortisol to cortisone ratio in these animals is low relative to that in human serum, suggesting that production of the MR protective enzyme, 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2), is increased in squirrel monkeys. Here, we directly evaluate whether increased production of 11β-HSD2, which inactivates cortisol to cortisone, is a mechanism for protection of MR. In vitro assays showed that 11β-HSD2 activity in squirrel monkey kidney microsomes was 3 to 7 times higher than that seen in kidney microsomes from pig or rabbit. 11β-HSD2 protein detected by Western blot analysis was 4 to 9 times greater in squirrel monkey microsomes than in pig or rabbit microsomes. Comparison of the effect of expression of either human or squirrel monkey 11β-HSD2 on MR transactivation activity showed similar inhibition of MR response to cortisol by both enzymes, indicating that the intrinsic activities of the human and squirrel monkey enzymes are similar. These findings suggest that one mechanism by which squirrel monkeys protect the MR from activation by high cortisol levels in the kidney is by upregulation of 11β-HSD2 activity through increased production of the enzyme.